Bilateral mirror aneurysms at the origin of the posteroinferior cerebellar artery: case report and review of the literature. (6th May 2010) - Mariniello, Giuseppe; Briganti, Francesco; Tortora, Fabio; Marseglia, Mariano; Maiuri, Francesco
Abstract : We report an exceptional case of symmetrical mirror aneurysms at the origin of the posterior inferior cerebellar arteries treated by endovascular occlusion. Questions related to a correct diagnosis and treatment at this localization are discussed.